Путешествие по России: стихи / Владимир Тяптин - Тяптин Владимир Яковлевич (Проект, 2014)
Экземпляры: ф.1 (20150127) / Инвентарный номер: 52598 / Цена: 180.91; 361.82 / Авт.знак: Т 99 / ГРНТИ: 17.82 /